Hepatitis C virus kinetics by administration of pegylated interferon-α in human and chimeric mice carrying human hepatocytes with variants of the IL28B gene. Issue 9 (7th November 2012) - Watanabe, Tsunamasa; Sugauchi, Fuminaka; Tanaka, Yasuhito; Matsuura, Kentaro; Yatsuhashi, Hiroshi; Murakami, Shuko; Iijima, Sayuki; Iio, Etsuko; Sugiyama, Masaya; Shimada, Takashi; Kakuni, Masakazu; Kohara, Michinori; et al.
Abstract : Objective: Recent studies have demonstrated that genetic polymorphisms near the IL28B gene are associated with the clinical outcome of pegylated interferon α (peg-IFN-α) plus ribavirin therapy for patients with chronic hepatitis C virus (HCV). However, it is unclear whether genetic variations near the IL28B gene influence hepatic interferon (IFN)-stimulated gene (ISG) induction or cellular immune responses, lead to the viral reduction during IFN treatment. Design: Changes in HCV-RNA levels before therapy, at day 1 and weeks 1, 2, 4, 8 and 12 after administering peg-IFN-α plus ribavirin were measured in 54 patients infected with HCV genotype 1. Furthermore, we prepared four lines of chimeric mice having four different lots of human hepatocytes containing various single nucleotide polymorphisms (SNP) around the IL28B gene. HCV infecting chimeric mice were subcutaneously administered with peg-IFN-α for 2 weeks. Results: There were significant differences in the reduction of HCV-RNA levels after peg-IFN-α plus ribavirin therapy based on the IL28B SNP rs8099917 between TT (favourable) and TG/GG (unfavourable) genotypes in patients; the first-phase viral decline slope per day and second-phase slope per week in TT genotype were significantly higher than in TG/GG genotype. On peg-IFN-α administration to chimeric mice, however, no significant difference in the median reduction of HCV-RNA levels and the induction of antiviral ISG was observed between favourable and unfavourable human hepatocyte genotypes. Conclusions: As chimeric mice have the characteristic of immunodeficiency, the response to peg-IFN-α associated with the variation in IL28B alleles in chronic HCV patients would be composed of the intact immune system.